Simple Past Tense Of The First Grade Students Of SMP Negeri 1 Seputih Banyak In Academic Year Of 2014/2015 - Qory Fahrunisa Firdaus (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
In teaching grammar, especially simple past tense, the teachers must have more ability on how to teach it. They can use kinds of methods and medium to support their teaching-learning process. One of the media which can be used in the class is short video. The use of short video as a media in learning a material can give any influence. The researcher conducted this research to find out whether there was any influence of using short video as a media in learning simple past tense. This research used experimental research as the research method. The subject of the research were the students of the first grade students of class VII.D(30 students) and class VII.E (30 students) of SMP Negeri 1Seputih Banyak in academic year of 2014/2015. To collect the data, the researcher gave pre-test to those two classes to measure the students’initial understanding about simple past tense before teaching learning process. After teaching learning process had been given, the students of both classes were tested again by given post-test to find the final result. The result of this research shows that using video as a media gives positive influencein learning simple past tense. It can be proved by the result of t-value which is 9.28. It shows that t-value is higher than the p-value at significance 5% is 2.00 and at significance 1% is 2.66. Therefore, it can be concluded that using short video gives positive influence in learning simple past tense. In other words, using short video helps the students to improve their understanding about simple past tense.